Ethnobotany, diversity and content of inorganic substances present in the foliage of forest species of medicinal interest in Viñales National Park, Cuba - Rodríguez Guerra, Yoel (2012)
Ethnobotanical, floristic, phytochemical relations were determined in eight forest species with medicinal use in the Viñales National Park, Pinar del Rio, Cuba, considered by UNESCO as Cultural Landscape of Humanity. The ethnobotanicalstudy was conducted through a participatory survey with the residents of communities ˝El Moncada˝, ˝Ancón (Valle)˝, ˝República de Chile˝ and ˝Los Acuáticos˝. The results show loss of traditional knowledge and relationship with the communities studied ethnomedically, except in the community of ˝Los Acuáticos ˝. The results enumerate 72 forest species with medicinal uses belonging to 45botanical families, being the most representative: Rubiaceae, Meliaceae and Boraginaceae. According to the floral composition for the 8 selected forest species there is a 50% floristic similarity, which form five clusters. The study of minerals from the foliage of the eight selected species showed low concentrations. The uses ofthese species as non-timber forest products with medicinal and other applications have disrupted natural ecosystems in Viñales National Park, and some species are listed as endangered.